Evolving Patterns (Oz, 2004)
From the production of non-standard mass-produced objects to the digital simulation of draperies, dZO explored several strategies integrating digital design technique into conceptual and formal architecture research. In this text we would like to present a series of concepts and techniques that emerged in our recent work including “weaving,” “iterative process,” and “evolving pattern.”